PENINGKATAN HASIL BELAJAR MURID MATERI AKSARA JAWA MELALUI PEMANFAATAN MEDIA “KARAWA” DI KELAS III ABU BAKAR AS-SIDDIQ SDIT MUHAMMADIYAH SINAR FAJAR - Firmansah, Fery; Fitri Dahhlia, Sophia; Tohirin; Mawaddaturrohmah, Via; Winarni, Wiwin; Dwi Pangesti, Yuli; Sri Hastuti, Yunia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the process of utilizing KARAWA (Javanese Script Cards) media and to demonstrate the improvement in student learning outcomes regarding Javanese script material in the Abu Bakar As-Siddiq third-grade class at SDIT Muhammadiyah Sinar Fajar during the 2025/2026 academic year. The study was motivated by low student learning outcomes in Javanese script material, attributed to conventional teaching methods, a lack of creative learning media, and low student motivation regarding this abstract and complex subject matter. This research is a Classroom Action Research (CAR) study conducted over two cycles—comprising planning, action implementation, observation, and reflection stages in each cycle—utilizing the Problem-Based Learning (PBL) model integrated with KARAWA media. The research subjects consisted of 28 third-grade students. Data were collected through formative tests/assessments, observation, and documentation, and subsequently analyzed using both qualitative and quantitative methods. The results showed a significant improvement: the class average score rose from 54.21 in Cycle I (with a classical mastery rate of 42.86% or 12 students achieving mastery) to 88.18 in Cycle II (with a classical mastery rate of 85.71% or 24 students achieving mastery), thereby meeting the established success indicator (≥85%). Beyond cognitive aspects, the implementation of KARAWA media also enhanced student engagement, collaboration, and critical thinking skills. It can be concluded that the use of KARAWA media is effective in improving Javanese language learning outcomes regarding Javanese script material for third-grade students in the Abu Bakar As-Siddiq class at SDIT Muhammadiyah Sinar Fajar.